Impact of Cage Culture On Water (physical and biological) Parameters in Batang Ai Hydroelectric Dam - Hii, King Ming (Universiti Malaysia Sarawak, UNIMAS, 2010)
Cage cultures are important aquaculture industry in Sarawak as they provide source of protein for the rapid growing of population and fulfilling high market demand on freshwater fishes. The Batang Ai Hydroelectric Dam is located at Lubok Antu, Sri Aman division Sarawak. The objective of this study was to evaluate the impacts of cage culture activities on the water quality (physical and biological parameters) of the Batang Ai Hydroelectric Dam. In-situ parameters and water samples were collected at four stations at fixed distances and depths. Temperature obtained showed that the value ranged from 25.22°C to 32.23°C, following the gradual decrease trend from the surface to the bottom water. Turbidity ranged from 0.019 NTU to 0.057 NTU whereas secchi depths were ranged from 78 cm to 190 cm and water clarity increased as distance increased from the cage. Total suspended solids falls in the range of 1.50mg/L to 9.10mg/L while pH was in the range of 6.18 to 7.34. Conductivity ranged from 33ms/cm to 89 ms/cm. Dissolved oxygen and biochemical oxygen demand increased and decreased respectively as distance was farer from the cages ranging from 0.26 mg/L to 8.45 mg/L and 6.860 mg/L² to 13.860 mg/L² . Chlorophyll a which ranged from 0.0044 to 0.4314 was the highest at station 3. The average low chlorophyll a concentration indicates that water body received low nutrient concentration to support the growth of phytoplankton. Only 3% of the samples collected recorded the presence of phytoplankton. Genus identified are Chroroococcus sp., Pediastrum sp., Nitzschia sp. and others. Turbidity, biochemical oxygen demand and total suspended solids were highest at station 3. This is most likely due to microbes’ activity on feed residues and waste discharges which consume high amount of oxygen. pH was lowest in station 2 and followed a gradual decreasing pattern from the surface to the bottom due to anaerobic and decomposing activity of residue that settled down. Low chlorophyll a and phytoplankton densities implied that cage culture activities were still below the carrying capacity of this reservoir. All physical and biological parameter values fall within Class I and Class II. Controlled and proper management of existing cage cultures will continue to maintain the water quality of Batang Ai Hydroelectric Dam.